2014
DOI: 10.2134/agronj14.0092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Fertilizer on Growth and Yield of Grain Sorghum Hybrids and Inbred Lines

Abstract: Grain sorghum [Sorghum bicolor (L.) Moench] is an important crop in semiarid regions of the world because of its drought tolerance. Nitrogen is one of the most limiting nutrients in crop production due to low availability and loss. We hypothesize that there are di erences in physiological and yield traits among grain sorghum genotypes in response to N. e objectives of this study were to determine the responses of sorghum genotypes (hybrids and inbred lines) to N fertilizer and the relationship between their ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
9
28
0
1
Order By: Relevance
“…Biomass and HI values of sorghum and the effect of rotation on these variables (biomass and HI) that we report here are in line with previous research (Mahama et al, 2014;Peterson and Varvel, 1989;Prihar and Stewart, 1991). A significant effect of various rotations on biomass and wheat HI was also reported (López-Bellido et al, 2000;Mrabet, 2011;Turner, 2004).…”
Section: Biomass and Harvest Indexsupporting
confidence: 92%
“…Biomass and HI values of sorghum and the effect of rotation on these variables (biomass and HI) that we report here are in line with previous research (Mahama et al, 2014;Peterson and Varvel, 1989;Prihar and Stewart, 1991). A significant effect of various rotations on biomass and wheat HI was also reported (López-Bellido et al, 2000;Mrabet, 2011;Turner, 2004).…”
Section: Biomass and Harvest Indexsupporting
confidence: 92%
“…It was also noted that soil aluminum caused significant stress for sorghum. The amounts of N, P, and K in soils are critical to determine fertilizer doses incorporated to soils to increase the yields of sorghum as well as other crops [30,31]. Small amount of nutrients, particularly Zn, Fe, and Mn applied by foliar spraying significantly promote the yield of crops [32].…”
Section: Introductionmentioning
confidence: 99%
“…Both per se performance and combining ability of the inbred parents have been used separately or in combination to predict hybrid performance for different crops including sorghum (Mahama et al, 2014;Kenga et al, 2006); maize (Kebede et al, 2013;Makanda et al, 2010) and rice (Xie et al, 2014). The aforementioned studies have reported positive correlations between inbred per se performance and their hybrid grain yield performance under both drought stress and non-stressed conditions in subtropical and tropical environments.…”
Section: Per Se Performance and Combining Ability Of Inbred Parentsmentioning
confidence: 99%
“…Differences in dry matter accumulation, which can be related to increased plant height and tiller numbers, and partitioning of dry matter at maturity into grain number and grain weight were found to significantly contribute to grain yield performance in maize (Borrás and Gambin, 2010;Tollenaar et al, 2004), and in sorghum (Mahama et al, 2014;van Oesterom and Hammer, 2008).…”
Section: Dissection Of Grain Yield Into Component Traitsmentioning
confidence: 99%
See 1 more Smart Citation